2019
DOI: 10.3390/ma12233943
|View full text |Cite
|
Sign up to set email alerts
|

White and Red Brazilian São Simão’s Kaolinite–TiO2 Nanocomposites as Catalysts for Toluene Photodegradation from Aqueous Solutions

Abstract: The presence of volatile organic compounds in groundwater is a major concern when it is used as a drinking water source because many of these compounds can adversely affect human health. This work reports on the preparation and characterization of white and red Brazilian São Simão’s kaolinite-TiO2 nanocomposites and their use as catalysts in the photochemical degradation of toluene, a significant volatile organic compound. The nanocomposites were prepared by a sol-gel procedure, using titanium bis(triethanolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…After calcination at higher temperatures, the bands in the 3200-3700 cm -1 region disappeared, which evidenced that kaolinite was transformed into metakaolinite, with further appearance of a broad band at 1050 cm -1 , characteristic of SiO 2 . Moreover, the change in the band structure in the 400-1250 cm -1 region originated from the kaolinite → metakaolinite transformation, which modified Al 3+ coordination from octahedral to tetrahedral [25][26][27][28]34,37,38]. The band at 950 cm -1 , assigned to the Si-O-Ti antisymmetric stretching vibration, has been proposed as evidence of nanocomposite formation (Kočí et al, 2011) [39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After calcination at higher temperatures, the bands in the 3200-3700 cm -1 region disappeared, which evidenced that kaolinite was transformed into metakaolinite, with further appearance of a broad band at 1050 cm -1 , characteristic of SiO 2 . Moreover, the change in the band structure in the 400-1250 cm -1 region originated from the kaolinite → metakaolinite transformation, which modified Al 3+ coordination from octahedral to tetrahedral [25][26][27][28]34,37,38]. The band at 950 cm -1 , assigned to the Si-O-Ti antisymmetric stretching vibration, has been proposed as evidence of nanocomposite formation (Kočí et al, 2011) [39].…”
Section: Resultsmentioning
confidence: 99%
“…The uses of layered solids to immobilize semiconductors such as titanium dioxide have attracted interest from various researchers on the last years [25][26][27][28][29], all this authors justify the use of layered solids due the increasing of specific surface area, synergistic effect during photodegradation process due the adsorption and photocatalysis enhancement, presence of transition metals that could induces the change of bandgap of semiconductor, and obviously the recyclability ability that are increased using this class of matrix.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature, pH, and the precursor solvent are crucial factors in determining the particle size and distribution of the metal oxide in clay supports. Research on TiO 2 /kaolinite using titanium isopropoxide demonstrated the role of the DMSO solvent in producing more space for the more homogeneous dispersion of TiO 2 , which furthermore determines the hydrophobicity and reactivity of the nanocomposite [ 97 ]. The impregnation method including wet impregnation consists of mixing a precursor salt with a clay suspension in a solvent and tuning the optimum pH.…”
Section: Clay Modificationsmentioning
confidence: 99%